ANALISIS KINERJA PERUSAHAAN YANG MELAKUKAN RIGHT ISSUE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2004)
The event of right issue in emerging market has known as part of seasoned equity offering. There are many hypothesis state negative respone from investor as well as positive effect. The research want to test the financial and operating performance of campaign that conducting right issue (1997-1999), especially company performance in two years before and after that event. This study uses the sample of 62 firms listed in the Jakarta Stock Exchange. The hypothesis are tested applying paired t-test and independent sample t-test the analysis. The ratios such as current ratio, ATO, NPM, Tobin's Q, and PER, have statistically not significant results. These results mean that the profitability and operating performance of sample have decline after conducted right issues, while liquidity performance have shown increasing value. After comparing with non-issuers sample, the results of such as leverage, asset turnover, operating profit margin and Tobin's q of issuers. Have shown statistically significant in part periods, while other ratios like current ratio, net profit margin, and PER have shown statistically not significant results in all of periods. This study also test the impact of right issues on performance of the stock return, the result that companies have significant (before conducted right issue) of its stock return compare with non issuers and market return.